The communication Between Diabetes and Alzheimer’s Disease: a study on diabetic patients referring to health centers in three cities of Khuzestan province - Madmoli, Mostafa; Madmoli, Mohammad; Khodadadi, Mahboobeh; Madmoli, Yaghoob (International Research in Medical and Health Sciences, 2019)
Introduction: Epidemiological studies suggest convincing evidence for a meaningful relationship between type 2 diabetes and dementia. It also shows that type 2 diabetes is a major cause of Alzheimer’s disease. Given the Iranian population’s profile of about 31 million middle-aged people, in the next two decades, older people will form a large population. On the other hand, the increase in Alzheimer’s in the elderly is due to the prevalence of this disorder and the adverse effects and adverse effects in the next two decades. And so far, quantitative research has been conducted to investigate the risk of Alzheimer’s disease in diabetic patients in Khuzestan province. Therefore, this study titled "The communication Between Diabetes and Alzheimer’s Disease: study on diabetic patients referring to health centers in three cities of Khuzestan province" was done. Materials and Methods: This retrospective cross-sectional descriptive study was conducted on diabetic patients hospitalized in Shoushtar, Behbahan, and Abadan, between 2015 to 2017. The files of these patients who were diagnosed with diabetes and referred to medical centers in the mentioned cities that were extracted from medical records of city hospitals and entered the study. Data were then entered into SPSS software version 20. Data were analyzed using descriptive statistics, analytical tests and the significance level of P <0.05. Results: In this study, the mean age of patients was 57.00 ± 46.23 years. A statistically significant relationship was found between diabetes and those with Alzheimer’s disease (p = 0.006). However, there was no significant relationship between diabetes and those with a history of cardiovascular disease (p = 0.09). There was no significant relationship between education and those with Alzheimer’s disease (0.06). But a statistically significant relationship was found between jobs with those with Alzheimer’s disease (0.003). Conclusion: In this study, there was a significant relationship between diabetes and those with Alzheimer’s disease. Therefore, this study showed the risk of Alzheimer’s disease in diabetic patients in the three mentioned cities. More epidemiological and clinical research is needed to investigate the relationship between these two diseases in a wider and larger volume.